Становлення і розвиток церковного братського руху у Волинській губернії у другій половині ХІХ – на початку ХХ ст. - Sazhok, Oksana; Сажок, Оксана (Східноєвропейський національний університет ім. Лесі Українки, 2013)
Досліджено зародження, розвиток, цілі та регіональні особливості церковного братського руху нової формації у Волинській губернії у другій половині ХІХ – на початку ХХ ст. Охарактеризовано мету, завдання, етапи становлення, основні види діяльності братств волинських міст, містечок та сіл у контексті внутрішньої політики Російської імперії. The aim of brotherhood movement was raising authority of the Orthodox Church as a spiritual foundations of autocracy. Volyn fraternity had to establish in the minds of the indigenous people of his land his everlasting unity of the Russian people. Tasks that rely on brotherhood (church landscaping, missionary, charitable, spiritual enlightenment), performed in different ways, depending on the area in which they operate, which had a confessional situation in which the social environment worked and what material means had in its disposal. Official registration of fraternities was the «Basic rules for the establishment of the Orthodox church brotherhoods» (1864). Based on these «Rules» in the Volyn province emerged about 90 such associations.
Formation and Development of the Church Fraternal Movement in the Volyn Province on the Second Half of the XIX and at the Beginning of XX Century.
Keywords: Російська імперія; Волинська губернія; церковні православні братства; внутрішня політика; церковні попечительства; Russian Empire; Volyn province; church orthodox fraternities; internal politics; church trusteeship